Strategi Komunikasi Pemasaran Bumdesa Dalam Meningkatkan Volume Penjualan Toko Bumdes Jaya Abadi Desa Toddopulia - Bintang Balele; Mahmud Mahmud; Nurlindah Nurlindah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research was conducted in Toddopulia Village, Tanralili District, Maros Regency. The purpose of this study is (1) To find out how the marketing communication strategy is carried out by BUMDes in increasing sales volume at the Jaya Abadi Bumdes Store, Toddopulia Village, Tanralili District, Maros Regency. (2) To find out what are the obstacles faced by BUMDes in increasing sales volume at the Bumdes Jaya Abadi Store, Toddopulia Village, Tanralili District, Maros Regency. The benefits of this research are (1). Theoretical Benefits.This research is expected to provide benefits and contribute to the development of Communication Science, especially social communication. (2). Practical Benefits. This research is expected to increase knowledge and insight about sales communication strategies.